2000
DOI: 10.1089/10430340050083243
|View full text |Cite
|
Sign up to set email alerts
|

Triple Transduction with Adeno-Associated Virus Vectors Expressing Tyrosine Hydroxylase, Aromatic-L-Amino-Acid Decarboxylase, and GTP Cyclohydrolase I for Gene Therapy of Parkinson's Disease

Abstract: Parkinson's disease (PD), a neurological disease suited to gene therapy, is biochemically characterized by a severe decrease in the dopamine content of the striatum. One current strategy for gene therapy of PD involves local production of dopamine in the striatum achieved by inducing the expression of enzymes involved in the biosynthetic pathway for dopamine. We previously showed that the coexpression of tyrosine hydroxylase (TH) and aromatic-L-amino-acid decarboxylase (AADC), using two separate adeno-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(99 citation statements)
references
References 43 publications
2
95
1
1
Order By: Relevance
“…14 Previous studies, including our own, have demonstrated that AAV vector-mediated delivery of dopamine-synthesizing enzymes results in efficient long-term expression of the transgene in the striatum. [14][15][16] The present study used the Sauer and Oertel partial PD model. 17 In this model, intrastriatal injection of 6-OHDA induces progressive retrograde degeneration of DA neurons that starts between 1 to 2 weeks after lesioning and continues over 8 to 16 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Previous studies, including our own, have demonstrated that AAV vector-mediated delivery of dopamine-synthesizing enzymes results in efficient long-term expression of the transgene in the striatum. [14][15][16] The present study used the Sauer and Oertel partial PD model. 17 In this model, intrastriatal injection of 6-OHDA induces progressive retrograde degeneration of DA neurons that starts between 1 to 2 weeks after lesioning and continues over 8 to 16 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The total number of complete body turns was counted during an observation period of Ն60 min, as described previously. 16 Spontaneous limb use was scored every 4 weeks using the cylinder test method. 10 Rats were placed in a clear glass cylinder large enough for free movement.…”
Section: Behavioral Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…ATP6V0C plays a central role in H + transport as one part of the multi-subunit complex of ATPase [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Israel and his group initially proposed that medatophore forms a proteinaceous pore by the six transmemebrane c subunits of ATPase [10,11].…”
Section: Mediatophore As An Ortholog Of Atpasementioning
confidence: 99%
“…Various vector systems have been used in recent preclinical studies to deliver different combinations of these enzymes. These include multicistronic lentiviruses simultaneously encoding GCH1, TH and AADC; 20 combinations of AAV vectors separately encoding GCH1 and TH 21 or GCH1, TH and AADC; 22,23 an HSV vector coexpressing AADC and TH. 24 In all cases, coexpression of the enzymes and functional recovery of the experimentally lesioned animals was observed.…”
Section: Delivery Of Transgenes Encoding Enzymes Involved In Dopaminementioning
confidence: 99%